(untitled) - Manjula Purushothaman, Mohd.Gousuddin Inamdar, Vasanthy Muthunarayanan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Various researchers, authors, government agencies and international agencies have defined E-waste in simple language. It provides better explanation and understanding regarding E-waste. Some definitions are included in this study to provide better understanding the concept of E-waste. The target population for this study has been selected from Chennai city of the State of Tamilnadu. The prime focus of the present study is the Consequences of E- Waste on human health and environment. This study also revealed the impact of E- Waste on mankind and providing awareness to companies, its consequences and the suggestions of the public regarding disposal of E-waste in a Chennai city and some other cities of Tamilnadu.